2008
DOI: 10.1007/s10350-008-9399-9
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Postoperative Pathway: Accelerating Recovery after Ileostomy Closure

Abstract: Ileostomy closure patients managed with postoperative care pathways can have a short hospital stay with acceptable morbidity and readmission rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 16 publications
3
37
2
Order By: Relevance
“…This likely requires more intensive postoperative care through higher acuity monitoring, measurement of physiologic parameters, and physician monitoring that may extend beyond the intraoperative environment [11]. It may be this patient cohort that benefits from clearly defined postoperative multidisciplinary team management, including the trend of clinical pathways to maximize overall care [2,4]. Clearly, patients with respiratory failure and sepsis will have more aggressive care needs, as these patients are typically being cared for in an intensive care setting; however, identification of patients preoperatively with more subtle changes such as a creatinine > 1.5 that may not raise an issue at first would not only herald a mandatory preoperative evaluation, but invoke a ''red-flag'' for closer observation perioperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This likely requires more intensive postoperative care through higher acuity monitoring, measurement of physiologic parameters, and physician monitoring that may extend beyond the intraoperative environment [11]. It may be this patient cohort that benefits from clearly defined postoperative multidisciplinary team management, including the trend of clinical pathways to maximize overall care [2,4]. Clearly, patients with respiratory failure and sepsis will have more aggressive care needs, as these patients are typically being cared for in an intensive care setting; however, identification of patients preoperatively with more subtle changes such as a creatinine > 1.5 that may not raise an issue at first would not only herald a mandatory preoperative evaluation, but invoke a ''red-flag'' for closer observation perioperatively.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the factors associated with successful postoperative recovery, surgeons are able to more clearly determine the optimal clinical management strategy for each individual patient and counsel patients better, allowing patients to make more informed decisions about their health care. Careful preoperative planning and risk factor analysis with modification, where possible, leads to improved perioperative care [2][3][4]. The purpose of this study was to identify perioperative factors associated with the development of acute renal failure and myocardial injury in an uncomplicated recovery, detect differences when associated with a major complication, and to understand who develops acute renal failure and myocardial infarction when divided based upon having a major surgical complication.…”
Section: Introductionmentioning
confidence: 99%
“…ICPs have been shown to be effective in improving care and clinical management in many surgical specialties13 14 and terminal care,15 but there seems less experience in acute medicine 16 17. The purpose of this study was to assess whether the introduction of an ICP for paracetamol poisoning would improve the management of this challenging patient group.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, multiple protocols to reduce the duration of postoperative ileus (POI) have been proposed, with varied success. 25,14,19 These include various pre-, intra-, and postoperative components in a variety of combinations and permutations. However, despite the research demonstrating that pathway use can accelerate GI recovery and decrease LOS, a recent survey found that approximately 30% of physicians who perform colectomies reside at a hospital with a perioperative care protocol for elective bowel resection that include components to accelerate GI recovery.…”
Section: Introductionmentioning
confidence: 99%